From shipbreaking to sustainable ship recycling : evolution of a legal regime - Puthucherril, Tony George (Legal aspects of sustainable development ;, 2010)
Ship recycling conserves resources, employs an unskilled workforce, and removes outdated tonnage. Operating mainly on the Indian subcontinent, this a ~primitivea (TM) industry often results in loss of human life and pollution of the marine environment. Despite moral indignation, the international community has struggled to manage this industry and only recently completed the IMO International Convention for the Safe and Environmentally Sound Recycling of Ships. Using the Indian experience on shipbreaking as a case study, this book assesses the strengths and weaknesses of the Convention. The au.